Instructional spending per student: patterns and explanations - Schulman, Steven, author; Academic Labor: Research & Artistry, publisher (Colorado State University. Libraries, 2019)
Most students know what they spend on tuition and other costs of attending college, but most do not know how much their colleges spend on their education in return. This paper provides figures on instructional spending per full-time equivalent student, broken down by institutional level and sector. Variations in this measure of educational spending can be substantial even among apparently similar institutions. A cross-sectional multiple regression model utilizing 2016 IPEDS data on every public and private non-profit college and university in the United States is used to explore the possible causes of these variations. It shows that instructional spending per student rises with the portion of the budget devoted to instruction. It falls with the non-tenure track portion of the instructional staff, with the prevalence of students from low-income backgrounds, and with tuition as a fraction of total revenue. These findings are mostly as expected, but most of the variation in instructional spending per student is still unexplained.
Keywords: instructional spending; higher education; students